Workshop on the Launching of AgDataHub Platform - Diarra, Afoussatou; Tandia, Safiatou; Koita, Bathiry (2024)
This report provides a comprehensive overview of the AICCRA workshop held on November 12, 2024, at Mali-Météo, Bamako. The event marked the launch of the AgDataHub platform, a digital tool designed to support agricultural decision-making by offering access to agro-climatic data, including short-term and seasonal weather forecasts, historical rainfall data, and satellite imagery. The workshop featured presentations on the achievements of the AICCRA project in Mali, fundamentals of seasonal forecasting, and Mali-Météo’s agrometeorological services. Participants engaged in practical demonstrations and exercises to familiarize themselves with the platform’s functionalities, such as data querying and analysis.